SUKUT AL-SYÂRI` DALAM PERSPEKTIF IMAM AL-SYATHIBY DAN KEHUJJAHANNYA DALAM IJTIHAD - Ikhlas, Al; Wardevi, Riza; Wiza, Rahmi (JURIS (Jurnal Ilmiah Syariah), 2017)
Islam is a perfect religion and there is no Samawi religion after Islam. All laws are derived from alShari (AllahSwt) and this has covered all forms of human behavior. All these provisions are revealed to the Prophet Muhammad PBUH. So this makes Rasulullah PBUH as the main source in teaching syari `at. However, after Rasulullah PBUH past away there is no more revelations that come down to humans. This is the problem among Muslims. On that basis, Imam al-Syathiby gave birth to the concept of sukut al-Syari ' as one method of ijtihad in answering the absence of legal proof in Islam.